WORK DISCIPLINE, MOTIVATION, AND EMPLOYEE LOYALTY: THE MEDIATING EFFECT OF JOB SATISFACTION - Donni Alnis Nasution; Ali Hanafi Nasution; Salwa Aprilia (Universitas Muhammadiyah Tangerang, 2026)
Purpose: This study aims to analyze the effect of work discipline and motivation on employee loyalty with job satisfaction as a mediating variable. The research addresses the problem of low employee loyalty reflected in lack of responsibility, inadequate recognition, and diminished commitment, as identified through preliminary surveys and absenteeism data.Methodology: A quantitative approach was employed using Structural Equation Modeling (SEM) with SmartPLS 3.0. The sample comprised 100 employees selected through proportionate stratified random sampling from a total population of 559 employees at PT Sungai Budi Group, Tangerang, Indonesia.Findings: Results indicate that work discipline and motivation positively and significantly affect job satisfaction. Work discipline and job satisfaction significantly influence employee loyalty. However, motivation does not have a significant direct effect on loyalty. Job satisfaction significantly mediates the relationship between work discipline and loyalty, but fails to mediate the motivation-loyalty relationship.Originality/Novelty: This research provides empirical evidence on the differential mediating role of job satisfaction, demonstrating that satisfaction functions as a mediator for disciplinary mechanisms but not for motivational drivers in the Indonesian manufacturing context. The findings challenge the assumption that motivation automatically translates into loyalty through satisfaction.Practical Implications: Companies should strengthen disciplinary systems and recognition programs while reevaluating motivational strategies that do not directly contribute to long-term employee loyalty. Attention to workload fairness and conducive work environments is essential for optimizing loyalty.